(untitled) (Journal of Economics, Law and Society, 2025)
Fueled by a remarkable year-on-year growth in 2022, reaching USD 30 billion, the global Takaful industry is experiencing a surge. The Gulf Cooperation Council (GCC), contributing a dominant 55.7% of global Takaful contributions, stands as a cornerstone of this growth. This study compares the financial metrics of Islamic (Takaful) and conventional insurance companies within the GCC region. Employing the System Generalized Method of Moments (SGMM) panel data estimator on a 10-year (2013-2022) sample of 85 insurance companies across six countries, the analysis reveals significant differences in the performances of the two insurance segments. Takaful companies generally exhibit lower capitalization, leverage, solvency, claim ratios, and firm size but demonstrate higher premium growth than their conventional counterparts. Furthermore, the study identifies economic growth as a key driver of profitability, while firm-specific factors like leverage, capital adequacy, and firm size also play a significant role. Interestingly, neither the business model nor the COVID-19 pandemic significantly impacted profitability, highlighting the industry’s adaptability and robust risk management practices. These findings offer valuable insights for stakeholders to make informed decisions on fostering growth, stability, and innovation within the GCC’s insurance landscape. Additionally, the research emphasizes the need for continuous analysis to adapt to evolving market conditions and regulatory environments and ensure long-term sustainability for the region’s insurance sector.